The Effect of the Quality of Health Services on the Satisfaction of Patients at the East Langsa Community Health Center - Desy Murdiatama; Ahmad Rifai; Indah Anggraeni (Journal La Medihealtico, 2021)
Service quality and patient satisfaction are the two most important things in Community Health Center (puskesmas) services. This study aims to see the effect of the quality of health services on outpatient satisfaction at Langsa Timur Public Health Center, Langsa City in 2020. This type of research is a quantitative research which is an analytical survey with a cross sectional study approach. The population in this study were 2,116 people. A sample of 95 people using the Slovin formula. The analysis used is univariate analysis, bivariate analysis with chi-square test and multivariate analysis with linear regression test, measuring instruments used questionnaires and data processing using computerized with a significance level of P-Sign <0.05. The results of this study are based on the results of univariate analysis, as many as 64 people were dissatisfied and 31 people were satisfied. The results of multivariate analysis showed that physical evidence and responsiveness had an influence on patient satisfaction and physical evidence was dominant. The conclusion of this study is that there is an effect of physical evidence and responsiveness on outpatient satisfaction at Langsa Timur Public Health Center, Langsa City.